Intraoperative Disasters During Minimally Invasive Esophagectomy - Thakur, Binay; Khatiwada, Sagar; Tiwari, Manoj; Bhattarai, Shachee; Adhikari, Mahesh Mani; Sapkota, Sandeep; Raut, Saujan; Thakur, Jessica (Nepalese Journal of Cancer, 2026)
Background: Intraoperative disasters remain a serious concern during Minimally Invasive Esophagectomy (MIE), however, it has never been properly reported. The aim of the study was to analyze the incidence, types, and management of intraoperative disasters encountered during MIE in a Tertiary Cancer Hospital in Nepal. Methods: A retrospective review of prospectively maintained database of 303 consecutive MIE cases for esophageal and gastroesophageal junction cancer performed at BP Koirala Memorial Cancer Hospital was conducted. Patients who underwent McKewon’s MIE (n=260), Ivor-Lewis (n=4) MIE and Transhiatal MIE (n=39) were included in the study. Intraoperative disasters were defined as catastrophic events leading to major bleeding or injury to vital structures during surgery. Results: Major intraoperative complications were observerved in 9 patinets (2.9%). Tracheo-bronchial (n=2), Thoracic duct (n=2), pulmonary parenchymal (n=2), SVC (n=1), and aortic (n=1) were detected intraoperatively and were managed with suture repair. One splenic injury was controlled with electrocauterization. None of the patients required conversion to open surgery. There was one 90-day mortality (1/9; 11%) among patients with intraoperative complications. Conclusion: Identification and prompt management of intraoperative complications are critical in minimizing post operative mortality. Our study may serve as a reference to compare and evaluate performance of MIE for cancer in Nepalese context.